0024 An evaluation of in vivo versus simulation suite delivered simulation-based mental health training for emergency department teams. (2nd November 2015) - Humphreys, Rosemary; Pathan, James; Attoe, Chris; Calvert, Simon; Cross, Sean
Abstract : Background: We developed an interprofessional simulation-based training (SBT) to promote collaboration when caring for patients in mental health crisis in the Emergency Department (ED). The intervention was run both in vivo and in a purpose-built simulation suite. The primary analysis of educational outcomes has been presented elsewhere. 1 Aims: To compare participant learning outcomes and experiences from in vivo versus simulation suite delivered SBT. Methods: A SBT was developed in which participants engaged in three scenarios of a simulated patient's journey through the ED followed by structured debriefs. One course was delivered in vivo whilst three courses, with identical content and format, were delivered in a simulation suite. Participants completed pre- and post-course questionnaires, measuring changes in knowledge, confidence and attitudes. Individual participant overall change in knowledge, confidence and attitudes were compared for both participant groups using Independent-Samples T and Mann Whitney U Tests. Post-course focus groups were conducted to gather qualitative data on participant experience. Results: 12 participants engaged in in vivo training versus 25 participants in simulation suite training. The professional mix was similar for both groups. The distribution of change in knowledge and self-rated confidence scores and attitudinal shift was not significantly different for in vivo and simulation suite groups ( p = 0 .64; p = 0 0.92; p = 0 .58). Views on the relative merits of in vivo versus simulation suite training were divergent. Participants from both groups recognised the tension between achieving environmental fidelity with in vivo simulation and the potential detrimental impact of managing distractions on learning. Conclusion: Previous work has demonstrated that SBT effectively increases participants' self-rated confidence and leads to positive attitudinal changes when caring for patients in mental health crisis in the ED. 1 Our results suggest that the effectiveness of learning does not appear to be different for in vivo versus simulation suite delivered training. Reference: Humphreys RA, Piette A, Wilson C, Kowalski C, Cross S. Mental health crisis in the emergency department: outcomes from a new interprofessional simulation. Royal College of Psychiatrists International Congress, 2015